Bioactivity of a synthetic peptide derived from a defensin from the tick Ornithodoros savignyi Audouin (1827) - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2014.